The importance of a specific warm-up on the performance of the handball goalkeeper - Dumitru, D. C. (Journal of Physical Education and Sport, 2010)
The aim of this paper is to determine the influence of a specific warm-up in the performance of the handball goalkeeper. To achieve this, the different aspects that influence the preparation of the player who occuppies this position, were examined. The samples chosen for this research consist of five handball playersaged between 17 and 28 years (M = 23) belonging to a Spanish female handball Club. The information was collected from the official match statistics of the first and second national Spanish League. The results obtained point to the need for a specific warm-up for the goalkeeper position because it significantly increases theperformance level of the player in this position, and shows the importance of the specific warm-up for the goalkeeper on the team results.